An empirical investigation of the Libyan audit market: perceptions of auditor's independence. (13th May 2010) - Faraj, Shamsaddeen Khamis; Akbar, Saeed
Auditor independence has received considerable attention in recent years. This is due to the fact that independently audited financial statements may result in the generation of true and fair accounting information which will help stakeholders to form rational expectations about firms and minimise the agency cost. It can also be argued that lack of independence would lead auditors to collaborate with the management of firms and would produce misleading accounting information. Accepting this premise, this study explores the effects of 12 different variables on the perceptions of auditor independence in Libya. A sample of five user groups namely owners, investors, lenders, managers and auditors were chosen for the survey. The results suggest that all user groups regard auditor independence as an important factor in forming their decisions about firms. Amongst other variables, the non-availability of auditing standards in Libya is found to be the strongest factor which undermines auditor independence in Libya.